ANALISIS PENGARUH INFLASI, SUKU BUNGA, DAN NILAI TUKAR (KURS) TERHADAP INDEKS HARGA SAHAM LQ45 YANG LISTING DI BURSA EFEK INDONESIA (BEI) - Sally Maria Bramana (KOLEGIAL, 2017)
The purpose of this study is to identify the influence of inflation, interest rate, and exchanges rate together and partially on LQ45 stock price index in Indonesia Stock Exchange. The methods of this study used associative design to determine the relationship between two or more variables. The instrument of this study using purposive sampling technique, and the total sample of 22 companies belonging to LQ45 companies registered from January 2012 to December 2016. The result shows LQ45 Stock Price Index listed on Indonesia Stock Exchange is influenced by inflation, interest rate, and exchange rate together, but partially inflation and interest rate do not affect the LQ45 Stock Price Index listed on the Indonesia Stock Exchange.